Spatial integration of fry and fractal analyses in regional exploration: a case study from bafq–posht-e-badam, iran (2010)
The goal of this study is to investigate the Fractal as well as Fry analysis which is implemented as complementary methods to evaluate their efficiency as regional exploration tools. The disadvantage of 'Box-counting' method lies in its inadequacy in dealing with low numbers of point data sets. Attempts have been made to use spatial integration of airborne geophysical data to turn this method to an useful tool for detecting the hidden mineralizations.According to the mineralization trends, resulted from Fry analysis using the Rose diagram of the faults within the area, has confirmed field observations concerning structurally controlled mineralization. This suggests that the fractal dimension in 'Box-counting's method must be similar for both mineralization points and fault lines but that is not the case for the study area. Furthermore, 'Number-in-circle' method has been applied to check the anomaly points whose fractal dimension has corresponded to that of the fault lines in 'Box-counting' method. The difference between fractal dimensions of mineralization points and those of fault system lies in the low number of recognized occurrences. As a matter of fact this issue can constract  as an exploration key in leading  to some promising areas that need more complementary surface as well as  underground survey. The significance of airborne geophysical survey in iron deposits mapping and prospecting is in providing some valuable information for better understanding the spatial pattern of mineralization as well as feeding exploration activities with new high-priority areas. This procedure can prove a useful technique to develop the spatial data modeling for regional exploration.